Determination of compatibility and stability of haloperidol and morphine mixtures used in palliative care (Brazilian Journal of Pharmaceutical Sciences, 2018)
With the aim of controlling various symptoms, possible to use mixtures of different drugs within infusion devices. This should take into account the compatibility of the mixture. Factors influence the compatibility and stability of the mixtures are: drug type, concentration, solvent, temperature and light. When evaluating the compatibility of the mixtures for infusion for subcutaneous via is important to consider infusion devices used and the conditions of light and temperature should simulate as far as possible the conditions in practice assistance. There are diverse studies that analyze the compatibility of drug mixtures, but there are still many possible combinations of drugs for which evidence is not available. The objective of this work is to study the compatibility and stability of several mixtures of haloperidol and morphine that can be used in solution for subcutaneous infusion.